2020
DOI: 10.1093/icesjms/fsz257
|View full text |Cite
|
Sign up to set email alerts
|

An integrated investigation of the effects of ocean acidification on adult abalone (Haliotis tuberculata)

Abstract: Ocean acidification (OA) and its subsequent changes in seawater carbonate chemistry are threatening the survival of calcifying organisms. Due to their use of calcium carbonate to build their shells, marine molluscs are particularly vulnerable. This study investigated the effect of CO2-induced OA on adult European abalone (Haliotis tuberculata) using a multi-parameter approach. Biological (survival, growth), physiological (pHT of haemolymph, phagocytosis, metabolism, gene expression), and structural responses (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 69 publications
(106 reference statements)
5
20
0
Order By: Relevance
“…Reduced growth in shell length and alterations of the shell microstructure were observed in juvenile abalone exposed to pH T 7.6, which correspond to projected pH values expected for 2100 (IPCC, 2014;Gattuso et al, 2015). Since these pH conditions corresponded to an aragonite saturation state below 1, it was concluded that the effects on shell growth and integrity were principally caused by direct aragonite dissolution within the abalone shell (Auzoux-Bordenave et al, 2020). Additional effects on the organic periostracum and nacre structure suggested that other processes involved in shell biomineralization, such as matrix protein production and enzymatic activities, would also be influenced by changes in seawater pH.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Reduced growth in shell length and alterations of the shell microstructure were observed in juvenile abalone exposed to pH T 7.6, which correspond to projected pH values expected for 2100 (IPCC, 2014;Gattuso et al, 2015). Since these pH conditions corresponded to an aragonite saturation state below 1, it was concluded that the effects on shell growth and integrity were principally caused by direct aragonite dissolution within the abalone shell (Auzoux-Bordenave et al, 2020). Additional effects on the organic periostracum and nacre structure suggested that other processes involved in shell biomineralization, such as matrix protein production and enzymatic activities, would also be influenced by changes in seawater pH.…”
Section: Introductionmentioning
confidence: 75%
“…Additional effects on the organic periostracum and nacre structure suggested that other processes involved in shell biomineralization, such as matrix protein production and enzymatic activities, would also be influenced by changes in seawater pH. Avignon et al (2020) demonstrated significant effects on growth in shell length, microstructure and resistance in adult H. tuberculata exposed to pH T 7.7. Although the aragonite saturation was above 1 (1.24) here, the effects on shell integrity were partly attributed to direct effects on aragonite dissolution.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Among marine calcifying molluscs (e.g. oysters, mussels, giant clams, abalones, limpets) negative impacts of temperature and p CO 2 have been demonstrated on the survival, growth, biomineralization processes and other key physiological functions on different stages of their life cycle ( Bougrier et al , 1995 ; Kurihara, 2008 ; McClintock et al , 2009 ; Gazeau et al , 2010 ; Welladsen et al , 2010 ; Melzner et al , 2011 ; Rodolfo-Metalpa et al , 2011 ; Schwartzmann et al , 2011 ; Talmage and Gobler, 2011 ; Liu et al , 2012 ; Watson et al , 2012 ; Kurihara et al , 2013 ; Fitzer et al , 2014 ; Le Moullac et al , 2016a , b ; Meng et al , 2018 ; Wessel et al , 2018 ; Avignon et al , 2020 ). However, effects of each stressor and their potential synergetic effect on giant clam’s physiology are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%